Characteristics of the elevation amplification effect of vibration velocity in rock surrounding underground cavities under different stress conditions. Issue 165 (February 2023) - Zhang, Tengsheng; Huang, Junhong; Li, Xinping; Liu, Tingting; Bian, Xing; Luo, Yi
Abstract: Side walls of deep underground cavities are commonly subject to dynamic disturbance of blasting excavation. To study the distribution of blasting vibration velocity in the side walls of underground cavities, the side walls were simplified as a mechanical model of simply supported slabs. Based on the field blasting vibration tests in the Taohuazui mining area in Hubei Province, China, a predictive formula for the peak particle velocity (PPV) in rock surrounding of cavities considering the geostress was deduced combining with dimensional analysis. The PPV in side walls of underground cavities under different geostress conditions was simulated using the LS-DYNA dynamic finite element software. The results show that the mechanical model of simply supported slabs is analogous to the vibration mode of side walls of underground cavities in the Taohuazui mining area: both show the amplification effect of PPV in the middle of the side walls. In addition, the prediction formula is highly consistent with the field measurements and numerical simulation results. With the increases in the geostress and the lateral pressure coefficient ( σ H / σ V ), the PPV on side walls always increases, while the overall trend remains unchanged. Highlights: Mechanical model of simply supported slab on side wall of underground cavern. The amplification effect of the PPV in the middle of the side walls persists. The effect of geostress on PPV is related to the distance between blasting centers. PPV increases with the increase of geostress and lateral pressure coefficient.